The effect of oral antiviral therapy for COVID-19 in managing non-hospitalized patients with lung cancer - Wan-Hsuan Hsu; Bo-Wen Shiau; Ya-Wen Tsai; Jheng-Yan Wu; Po-Yu Huang; Min-Hsiang Chuang; Ting-Hui Liu; Chih-Cheng Lai; Tzu-Chieh Weng (Elsevier, 2024)
Backgrounds: The effectiveness of oral antiviral therapy including nirmatrelvir plus ritonavir and molnupiravir in managing COVID-19 among individuals with pre-existing lung cancer was unclear. Therefore, this study was conducted to evaluate the usefulness of antiviral agents in the management of COVID-19 among patients with lung cancer. Methods: Utilizing data from the TriNetX - a global health research network, a retrospective cohort study was conducted involving 2484 patients diagnosed with both lung cancer and COVID-19. Propensity score matching (PSM) was employed to create well-balanced cohorts. The study assessed the primary outcome of all-cause hospitalization or mortality within a 30-day follow-up. Results: After PSM, the oral antiviral group exhibited a significantly lower risk of the primary composite outcome compared to the control group (6.1 % vs. 9.9 %; HR: 0.60; 95 % CI: 0.45-0.80). This association was consistent across various subgroups according to age, sex, vaccine status, type of oral antiviral agent, and lung cancer characteristics. Additionally, the oral antiviral group showed a lower risk of all-cause hospitalization (HR: 0.73; 95 % CI: 0.54-0.99) and a significantly lower risk of mortality (HR: 0.16; 95 % CI: 0.06-0.41). Conclusion: The study suggests a favorable impact of oral antiviral therapy on the outcomes of COVID-19 in individuals with lung cancer and support the potential utility of oral antiviral agents in improving outcomes in this vulnerable population.